Influences of Macropores on Infiltration into Seasonally Frozen Soil - Demand, D. (2020)
Brilliant Blue FCF (BB) was sprinkled on four plots equipped with soil moisture and temperature probes to mark flow paths. Frozen layer thickness was measured with infrared thermography of soil sections and overlaid with BB images. The frost depth of the experiments was 8 to 15 cm. Infiltration rates showed reduced infiltration compared with unfrozen conditions. By impeding refreezing of the infiltrating water with added NaCl, infiltration rates of 23 to 29 mm h−1 were measured. Without the addition of salt, the infiltration rates decreased to 5 to 10 mm h−1, attributed to pore blockage by refreezing water. Temperature measurements revealed that the frozen layer only thawed close to the soil surface during the experiments. Blue‐stained areas indicated that water was channeled through the frozen layer into the unfrozen soil. In addition, the soil moisture probes below the frozen layer measured an increase in unfrozen water content, whereas total water content in the frozen layer was constant. These observations were explained by a connected air‐filled porosity, such as biopores, which allowed water flow even under high initial water contents. These results illustrate the importance of macroporosity in relation to frost depth in controlling the infiltrability of seasonally frozen soils.